BUILD DESIGN APPLICATION TRACKING ORDER AT PT. ARTHA WAHANA AGROTAMA - Priyawan, Ageng Yudha; Eko Wulandari, Sri Hariani; Santoso, Rudi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
PT. Artha Wahana Agrotama is a company engaged in the sale of farm machine. PT. Artha Wahana Agrotama still using manual methods for day-to-day business, such as recording order transactions, payment archive, searches the archive, making reports, and memoranda. This recording methods for saving valuable information can be risky, for example loosing the information and taking up much space. To overcome the problems above, researcher is designing and implementing an application to simplify the administering for admin. The result from this information system is order and payment reporting. So, this application can overcome the company’s tracking order problem and give economical valuable information.